Report from the fifth international consensus meeting to harmonize core outcome measures for atopic eczema/dermatitis clinical trials (HOME initiative) - Chalmers, J.R.; Thomas, K.S.; Apfelbacher, C.; Williams, H.C.; Prinsen, C.A.; Spuls, P.I.; Simpson, E.; Gerbens, L.A.A.; Boers, M.; Barbarot, S.; Stalder, J.F.; Abuabara, K.; et al. (Wiley, 2018)
This is the report from the fifth meeting of the Harmonising Outcome Measures for Eczema initiative (HOME V). The meeting was held on 12–14 June 2017 in Nantes, France, with 81 participants. The main aims of the meeting were (i) to achieve consensus over the definition of the core domain of long-term control and how to measure it and (ii) to prioritize future areas of research for the measurement of the core domain of quality of life (QoL) in children. Moderated whole-group and small-group consensus discussions were informed by presentations of qualitative studies, systematic reviews and validation studies. Small-group allocations were performed a priori to ensure that each group included different stakeholders from a variety of geographical regions. Anonymous whole-group voting was carried out using handheld electronic voting pads according to predefined consensus rules. It was agreed by consensus that the long-term control domain should include signs, symptoms, quality of life and a patient global instrument. The group agreed that itch intensity should be measured when assessing long-term control of eczema in addition to the frequency of itch captured by the symptoms domain. There was no recommendation of an instrument for the core outcome domain of quality of life in children, but existing instruments were assessed for face validity and feasibility, and future work that will facilitate the recommendation of an instrument was agreed upon. The Harmonising Outcome Measures for Eczema (HOME) initiative is an international group working together to develop a core outcome set (COS) for clinical trials in eczema (synonymous with atopic eczema and atopic dermatitis). HOME is coordinated from the Centre of Evidence Based Dermatology, University of Nottingham, U.K. Participation in HOME is open to anyone with an interest in outcomes for eczema. A COS is the agreed upon minimum set of instruments that should be included in all clinical trials for a particular condition. Use of a COS does not preclude using other instruments; other domains and instruments can also be included to meet the specific requirements of individual trials. COS initiatives are active across many fields of medicine and should enable better synthesis of trial data and reduce selective outcome reporting bias. The HOME initiative follows the best current guidance on developing a COS. Four core domains have been identified: clinician-reported signs; patient-reported symptoms; quality of life; and long-term control. The core outcome measurement instruments for clinician-reported signs and patient-reported symptoms have been established: the Eczema Area and Severity Index (EASI) for measuring clinician reported signs was agreed on at the HOME III meeting, and the Patient-Oriented Eczema Measure (POEM) was chosen to measure patient-reported symptoms at the HOME IV meeting. This is a report from the fifth consensus meeting of the HOME initiative (HOME V), which was held on 12–14 June 2017 in Nantes, France. The local organizers were Sebastien Barbarot and Jean-Francois Stalder of Nantes University Hospital, France.